FILSAFAT ISLAM DALAM ILMU USHUL FIQIH - Riza Zahriyal Falah (Program Studi Hukum Keluarga Islam, 2015)
Building law (jurisprudence) Islam is composed of a lot of knowledge from the Quran Ulumul, Ulumul hadith, logic, language, fiqh usul, fiqh, and others. Usul Fiqh as ijtihad or express legal guidelines on a proposition and vice versa, has a very important position that must be mastered by the mujtahid scholars. Historically, Muslims introduction to the philosophy (outside Islam) has added science and knowledge. Philosophy is essentially thought. Systematic thinking. Same with philosophy, usul fiqh in practice is a deep thinking activities undertaken mujtahid to remove or excavate a particular law of a proposition, and vice versa. This leads to systematic thinking similarities there are some philosophical concepts adopted by usul fiqh such as the concept of analogy that compares a law with other laws, also the necessary linguistic analysis in text analysis. Formation reason Arab Abid al-Jabri which divides logical rational thinking Arab Islam into three, namely reason bayani, Burhani, and Irfani, also confirmed that the reason bayani developed by Muslims have made progress sciences dealing with religion. The concept of rational thought, but not independent of religiosity, could eventually develop ushul fiqh proven and relevant even today.